Solving the taxonomic identity of South American Pseudognaphalium viravira s.l. (Gnaphalieae, Asteraceae) - Freire, Susana E.; Grossi, Mariana A.; Monti, Claudia; Bayón, Néstor D. (Phytotaxa, 2025)
Pseudognaphalium (Gnaphalieae, Asteraceae) consists of about 60 species mainly distributed in South, Central, and North America, but some also occurring in Africa and Asia. The South American P. viravira was treated as a polymorphic species, ranging from a few centimetres to nearly half a meter tall, usually woolly with stem leaves varying from linear to linear-obovate and commonly numerous capitula arranged in dense terminal clusters. In major reviews of the species, nine heterotypic taxa have been considered synonymous with or morphologically similar to P. viravira. Recent molecular analysis puts three of them (P. andicola, P. montevidense and P. versatile) in distinct clades. In order to evaluate species limits on a morphological basis, we performed a morphometric analysis. A matrix of 31 morphological characters and 68 specimens were analyzed using two multivariate approaches: Cluster analysis and Principal Coordinate Analysis. Both, the dendrogram and the Principal Coordinate Analysis (PCoA) showed that the segregate species are not clearly distinguished in morphology. No discriminating morphological characters for these species have been found. In conclusion, all available data support that P. andicola, P. montevidense, and P. versatile should be considered synonyms of P. viravira. Pseudognaphalium viravira (including P. andicola, P. montevidense, and P. versatile) is described and illustrated.